XRD/SEM characterization of MOF with catalytic activities - Wong, Robin Zhi Cai (2018)
A zeolitic imidazolate framework, ZIF-8, was prepared via facile synthesis by mixing either Zinc nitrate hexahydrate, Cobalt (II) nitrate hexahydrate, or both in different compositions in organic solvent under room temperature. The effects of synthesis in the presence or absence of a modulating ligand, 1-methylimidazole, was studied and to obtain a description of the material. Herein, the morphology, composition, and structure of the polycrystalline ZIF-8 samples were characterized using X-ray diffraction (XRD), Scanning electron microscopy (SEM) and Energy Dispersive X-ray (EDX). The characterization was done over a range of samples with different ratios of Zinc and Cobalt metal ions added during the synthesis methods. By substitution of zinc with cobalt in different ratios, a series of Bimetallic ZIF (Cox·Zn1−x(MeIm)2) nanoparticles were obtained. These samples were observed and were successful in the synthesis procedure, and the preparation method was deemed to be reliable and repeatable. X-ray diffraction results and Rietveld refinement also showed that the lattice parameters were different in various compositions of Zinc and Cobalt, but did not have major disruptive changes. This can be attributed to the basis that Zinc and Cobalt have very similar atomic radius, and their substitution will not disrupt the structure. It was found that in the absence of 1-methylimidazole, the crystals synthesized were of far smaller dimensions. It was also observed that in the absence of 1-methylimidazole, the powders were not easily disperesed in the organic solvent methanol. In addition, the monodispersity of the ZIF-8 crystals was much higher for those synthesized with 1ml of 1-methylimidazole. These observations demonstrate the function of modulating monodentate ligands in the tuning of the crystal size as well as contributing to stability of the particles.